Does Working Memory Moderate the Within-Person Associations Between Pain Intensity and Negative Affect and Pain's Interference With Work Goal Pursuit?. Issue 6 (June 2018) - Mun, Chung Jung; Karoly, Paul; Okun, Morris A.
Abstract : Objectives: Chronic pain exerts a pervasive negative influence on workers' productivity. However, a paucity of research has addressed the mechanisms underlying the pain → productivity relation. In the present study using intensive daily diary data, we examined whether working memory (WM) moderates the positive within-person associations between (1) morning pain intensity and (2) morning negative affect (NA) and later day pain's interference of work-goal (WG) pursuit. Methods: A community sample of 131 adults with chronic pain completed a battery of questionnaires, laboratory-measured WM, and a 21-day daily diary. Results: WM did not moderate the positive within-person association between morning pain intensity and afternoon/evening ratings of pain's interference with work goal pursuit. However, individuals with higher WM showed significantly attenuated positive within-person association between morning negative affect and pain's interference with afternoon/evening work goal pursuit. Discussion: WM appears to protect goal-relevant information from distractions due to negative affective arousal. The continued use of ecologically valid observational and intervention studies would shed further light on the influence of WM on the pursuit of valued work goals in the face of pain and negative affect.